2004
DOI: 10.1002/dc.20161
|View full text |Cite
|
Sign up to set email alerts
|

Erdheim‐Chester disease of the brain: Cytological features and differential diagnosis of a challenging case

Abstract: Erdheim-Chester disease (ECD) is an uncommon, systemic xanthogranulomatous disorder, with distinct clinicopathological features, that is rarely expected preoperatively. We describe a case that presented in the brain of a 26-yr-old male patient and clinically mimicked the appearance of a neoplasm. The final diagnosis was a surprise. In retrospect, the diagnosis was suggested by the intraoperative "squash" preparations, which demonstrated a mixed cellular proliferation of lymphohistiocytic elements and large, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…2,5,12 This finding is also in contradistinction to the focal mass lesions reported in the supratentorial compartment. 12,14,15,19,20 The final patient demonstrated diffuse FLAIR signal-intensity hyperintensity, similar to findings in a previous report by Bianco et al 21 HPA involvement has been reported as a single micronodular or nodular infundibular stalk mass 5 or thickening of the pituitary stalk. 12 This is similar to the findings in 3 patients in our study who demonstrated linear thickening of the pituitary stalk.…”
Section: Discussionsupporting
confidence: 87%
“…2,5,12 This finding is also in contradistinction to the focal mass lesions reported in the supratentorial compartment. 12,14,15,19,20 The final patient demonstrated diffuse FLAIR signal-intensity hyperintensity, similar to findings in a previous report by Bianco et al 21 HPA involvement has been reported as a single micronodular or nodular infundibular stalk mass 5 or thickening of the pituitary stalk. 12 This is similar to the findings in 3 patients in our study who demonstrated linear thickening of the pituitary stalk.…”
Section: Discussionsupporting
confidence: 87%
“…Lumbar puncture is not recommended since ECD histiocytes rarely appear in the cerebrospinal fluid [36]. The differential diagnosis of ECD related intracranial lesions is wide: Intracerebral histiocytic lesions may mimic a neoplasm of glial origin [37]. Lesions of the cerebellum and brainstem may appear similar to demyelinating diseases such as multiple sclerosis [38].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, unlike most intracranial lesions, cerebellar lesions appear to have no mass effect. Histological examination of these lesions reveals extensive loss of myelin sheath with gliosis and marked sparing of axons [37,46]. A variety of symptoms correlate with brainstem and cerebellar involvement of ECD.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, we are aware of only one other case report describing the cytologic features of ECD in the literature. [18] In this other case report, the diagnosis of ECD was made on an intraoperative squash preparation from a brain lesion of a 26-year-old young man. The squash preparations showed a mixed cellular proliferation of lymphohistiocytic elements along with large, multinucleated cells with vesicular nuclei, prominent nucleoli and abundant cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Therefore, the aim of this report is to share the unique cytomorphologic findings in another case of ECD and to highlight the key cytologic features that were helpful in reaching this challenging diagnosis.…”
Section: Introductionmentioning
confidence: 99%